Exploring The Impact Of Customer-Focused Strategies On Boosting Innovation Performance In Enterprises - Xu, Lijuan; Guo, Hui; Nachiangmai, Suprawin (Migration Letters, 2024)
This study explores the complex connection between customer focus and business innovation performance, with a particular focus on the dynamic talents needed to effectively adapt in the digital economy. The paper presents a new conceptual model that combines dynamic capacity theory and innovation theory to address the lack of information about how external knowledge influences creativity in organizations. The study suggests that customer orientation has an impact on innovation performance by means of two intermediary factors: digital capacity and organizational creativity. The interaction between these factors enables the renewal and reorganization of the enterprise’s knowledge base, promoting a culture that encourages innovation. The suggested model is supported by empirical data obtained from a thorough survey of managers in 20 provinces and 3 municipalities in China. The findings suggest that companies that prioritize customer satisfaction improve their capacity to use digital technology and foster creativity inside the firm, ultimately leading to more innovation. The study demonstrates a sequential mediation framework, where digital capacity enhances organizational creativity, collectively mediating the beneficial association between customer orientation and innovation performance. The paper makes two theoretical contributions. Firstly, it provides a detailed explanation of how customer orientation affects innovation by including ordered chain mediating factors. This study builds upon prio[1]r studies that predominantly concentrated on the direct influence of client orientation on innovation. Furthermore, the study enhances comprehension of the role of dynamic skills, particularly digital capacity and organizational creativity, in facilitating the conversion of customer orientation into innovation capability. The implications for management practice indicate that cultivating a customer-centric company mindset is essential for organizations aiming to achieve greater innovation performance. Furthermore, adopting the digital economy involves enhancing digital skills, therefore enabling digital transformation and innovative initiatives to boost organizational creativity and overall innovation performance.